An Analysis of Acquiring the First Language Acquisition for the Child of a 3 Years Old Blumbungan Pamekasan (Conference on English Language Teaching, 2023)
To generate and use the word or sentence requires a science or field to discuss it, and the theory is psycholinguistics. Psycholinguistics covers three main points, Language production, perceptions of language and language acquisition. Language production refers to the process involved in creating and conveying meaning through language. Perceptions of language refer to processes involved in interpreting and understanding both written and spoken languages. Language mastery refers to the process of getting a native language or a second language.The researcher formulates one research focuses in this research, How does the child get the first language in psycholinguistics based on the piaget jean's perspective? So the goal of the focus of the problem is to describe how the child gets the first language in psycholinguistics according to the piaget jean's perspective.The researcher use qualitative research approach especially descriptive research. The data taken from the a child interacts with his friends as well as between his parent and how a child recognizes each surrounding object, and also interviewing the parents in child's intellectual development in every day. Data analysis indicates that children can speak their first words or first language of Madura at less than 3 years of age.